ปัจจัยที่เกี่ยวข้องและการสร้างแบบคัดกรองผู้มีความเสี่ยงต่อการเกิดอาการทางระบบกระดูกและกล้ามเนื้อหลังส่วนบั้นเอวในผู้ที่ทำงานในสำนักงานในจุฬาลงกรณ์มหาวิทยาลัย - ภัทริยา มูลกาย (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The objectives of this cross sectional study were to determine related factors of low back symptoms and to develop screening questionnaire for the risk of such symptoms among the office workers in Chulalongkorn University. Convenience sampling technique was used to select 403 office workers in Chulalongkorn University. Data was then collected by using self-administered questionnaire and physical examination. Two multiple logistic regressions were analyzed, treating low back symptoms in the previous 4 weeks and 12 months as binary outcomes, to identify their potential related factors for inclusion in the screening questionnaires. Sensitivity and specificity, as well as the Receiver Operating Characteristic (ROC) curve, were analyzed to determine the efficacy of the newly-constructed screening questionnaires. The results showed that factors which were related with low back symptoms in the previous 12 months and were used as a screening questionnaire included educational level, previous history of working as office worker, frequent forward bending, stress and poor flexibility of lumbar spine. The total scores were 15 and optimal cut-off score was 7. The sensitivity and specificity were 61.9 % and 70.8% respectively. When low back symptoms in the previous 4 weeks was the outcome, its related factors (which were also utilized in the screening questionnaire) consisted of previous history of working as office worker, years of working as office worker, frequent forward bending, standing more than 2 hours/day, using chair without lumbar support, imbalance between effort and reward ratio and poor flexibility of lumbar spine. The total scores were 14 and optimal cut-off score was 5. The sensitivity and specificity were 74.2 % and 63.4% respectively. In conclusion, this study proposes two screening instruments for identifying individuals at higher risk for low back symptoms among office workers. However, their effectiveness should be further verified by prospective study design.